Ultrasmall Fe3O4 nanoparticles on MXenes with high microwave absorption performance - Liu, Peijiang (2020)
Herein, 2D hierarchical composites of nano-sized Fe3O4 particles on MXenes (TiO2/Ti3C2Tx/Fe3O4) were synthesized by using a moderate hydrothermal reaction. Electron microscope techniques indicated that the surfaces of MXenes were densely covered with Fe3O4 nanoparticles of ∼4.9 nm. Microwave absorption capabilities in terms of the maximum reflection loss (RL) and effective bandwidth were investigated. Specifically, the TiO2/Ti3C2Tx/Fe3O4 exhibited a remarkable absorption performance, with a maximum reflectivity of −57.3 dB at 10.1 GHz and a band range below −10 dB to over 9.1–11.1 GHz at a thickness of 1.9 mm. Therefore, our 2D MXene composites are expected to be promising candidates as ultrathin and lightweight absorbing materials.